Pengembangan Platfrom Teknologi Inovatif Untuk Efisiensi Produksi UMKM (2024) - Nana Erika; Nailatun Nadrah; Ramada Sandi (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in supporting national economic growth and expanding employment opportunities in Indonesia. However, many MSMEs still face significant challenges in improving production efficiency due to limited human resources, low levels of technology adoption, and suboptimal operational management. To address these issues, this study developed an innovative digital technology platform designed to help MSMEs enhance productivity, reduce material waste, and accelerate the production process. The platform integrates Internet of Things (IoT), Artificial Intelligence (AI), and simplified Enterprise Resource Planning (ERP) technologies tailored for small business operations. Through IoT, production processes can be monitored in real time; AI is applied to analyze sales data and predict material requirements and production schedules; while the ERP system automates inventory, transaction, and financial reporting processes. Trials conducted across MSMEs in the food, handicraft, and textile sectors demonstrated a 30% improvement in production efficiency and a 20% reduction in operational costs. The results indicate that the implementation of innovative technological platforms can significantly enhance efficiency, accuracy, and competitiveness among MSMEs. Digital transformation not only increases production efficiency but also enables broader business integration into the global market through cloud-based systems. Government and institutional support are essential to expand the adoption of such technologies, ensuring that Indonesian MSMEs become more adaptive, productive, and sustainable in the era of Industry 4.0.